Performance improvement of bearingless multi-sector PMSM with optimal robust position control - Valente, Giorgio; Formentini, Andrea; Papini, Luca; Zanchetta, Pericle; Gerada, Christopher (IEEE, 2018)
Bearingless machines are relatively new devices that consent to suspend and spin the rotor at the same time. They commonly rely on two independent sets of three-phase windings to achieve a decoupled torque and suspension force control. Instead, the winding structure of the proposed multi-sector permanent magnet (MSPM) bearingless machine permits to combine the force and torque generation in the same three-phase winding. In this paper the theoretical principles for the torque and suspension force generation are described and a reference current calculation strategy is provided. Then, a robust optimal position controller is synthesized. A Multiple Resonant Controller (MRC) is then integrated in the control scheme in order to suppress the position oscillations due to different periodic force disturbances and enhance the levitation performance. The Linear-Quadratic Regulator (LQR) combined with the Linear Matrix Inequalities (LMI) theory have been used to obtain the optimal controller gains that guarantee a good system robustness. Simulation and experimental results will be presented to validate the proposed position controller with a prototype bearingless MSPM machine.